Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

How would I show that
$$J_1(x)+J_3(x)=\frac 4x J_2(x)$$
Using the series definition of the Bessel Function, which is
$$J_p(x)=\sum ^\infty _{n=0} \frac{(-1)^n}{\Gamma(n+1)\Gamma(n+1+p)}\left(\frac x2\right)^{2n+p}$$

I know that it can be achieved using some reindexing, but I am not sure how. I would greatly appreciate any help. Thank you.

share|improve this question

2 Answers 2

Yes, there is an index shift. Rewrite

$$J_1(x) = \frac{x}{2} + \sum_{n=1}^{\infty} \frac{(-1)^n}{n!(n+1)!} \left ( \frac{x}{2} \right ) ^{2 n+1}$$

$$J_3(x) = \sum_{n=1}^{\infty} \frac{(-1)^{n-1}}{(n-1)!(n+2)!} \left ( \frac{x}{2} \right ) ^{2 n+1}$$

Then

$$\begin{align}J_1(x)+J_3(x) &= \frac{x}{2} + \sum_{n=1}^{\infty} (-1)^n \left [ \frac{1}{n! (n+1)!} -\frac{1}{(n-1)! (n+2)!} \right ]\left ( \frac{x}{2} \right ) ^{2 n+1}\\ &= \frac{x}{2} + 2 \sum_{n=1}^{\infty} \frac{(-1)^n}{n!(n+2)!} \left ( \frac{x}{2} \right ) ^{2 n+1} \\ &= \frac{4}{x} \left[\frac{1}{2} \left ( \frac{x}{2} \right )^2 + \sum_{n=1}^{\infty} \frac{(-1)^n}{n!(n+2)!} \left ( \frac{x}{2} \right ) ^{2 n+2} \right ]\\ &= \frac{4}{x}\sum_{n=0}^{\infty} \frac{(-1)^n}{n!(n+2)!} \left ( \frac{x}{2} \right ) ^{2 n+2} \\\therefore J_1(x)+J_3(x) &= \frac{4}{x} J_2(x) \end{align}$$

share|improve this answer

Obtain $J'_2(x)$ in two ways using following relations.(These identities can be (easily) established by direct substitution of the provided series for $J_n(x)$ and I have provided these proofs and the end) :

$$ \frac{d}{dx}(x^2J_2(x))=x^2J_1(x)$$ $$ \frac{d}{dx}(x^{-2}J_2(x))=-x^{-2}J_3(x)$$

now expanding the parentheses (differentiation of multiplication) we arrive at :

$$ J'_2(x)=\frac{-2}{x}J_2(x)+J_1(x)$$ $$J'_2(x)=\frac{2}{x}J_2(x)-J_3(x) $$

subtracting the two relations from each other, we arrive at the requested identity.

(Proof of the first identity: $$\frac{d}{dx}(x^2J_2(x))=\sum ^\infty _{n=0} \frac{(-1)^n(n+2)}{\Gamma(n+1)\Gamma(n+3)} (\frac x2)^{2n+3}=$$$$\sum ^\infty _{n=0} \frac{(-1)^n}{\Gamma(n+1)\Gamma(n+2)} (\frac x2)^{2n+3}=x^2J_1(x)$$proof of the second:$$\frac{d}{dx}(x^{-2}J_2(x))=\sum ^\infty _{n=0} \frac{(-1)^nn}{\Gamma(n+1)\Gamma(n+3)}\left(\frac x2\right)^{2n-1}=$$$$\sum ^\infty _{n=1} \frac{(-1)^nn}{\Gamma(n+1)\Gamma(n+3)}\left(\frac x2\right)^{2n-1}=$$$$\sum ^\infty _{n=0} \frac{(-1)^{n+1}}{\Gamma(n+1)\Gamma(n+4)}\left(\frac x2\right)^{2n+1}=-x^{-2}J_3(x)$$)

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.